Impactos das políticas de avaliação da pós-graduação scrito sensu sobre o trabalho docente no Brasil: estudo de caso de uma instituição pública federal de ciência e tecnologia em saúde - Salvá, Maria Nair Rodrigues (2013)
This research aims to identify and analyze the changes in the teaching of the Postgraduate studies, due to the evaluation policy adopted by CAPES, in the period 1990-2010, from a study in a program post-graduate studies in Public Health in Federal Public Institution for Science and Technology in Health. To develop this analysis, the theoretical framework is presented a review of the literature on the CAPES evaluation system, as well as major changes that occurred in world of work and in education. The case study was conducted through semi-structured interviews. Based on the literature and conducting field research, it was concluded that changes to teaching against the implementation of the criteria adopted by CAPES evaluation of programs for post-graduate studies, manifested in "academic productivism", the "intensification of the work of teaching and the development of pathological problems to the teacher," the "changing role of the teacher in a knowledge society" and the "alienation of teaching."